Task-specific transfer of perceptual learning across sensory modalities - McGovern, David P.; Astle, Andrew T.; Clavin, Sarah L.; Newell, Fiona N. (Elsevier (Cell Press), 2016)
It is now widely accepted that primary cortical areas of the brain that were once thought to be sensory-specific undergo significant functional reorganisation following sensory deprivation. For instance, loss of vision or audition leads to the brain areas normally associated with these senses being recruited by the remaining sensory modalities [1]. Despite this, little is known about the rules governing crossmodal plasticity in people who experience typical sensory development, or the potential behavioural consequences. Here, we used a novel perceptual learning paradigm to assess whether the benefits associated with training on a task in one sense transfer to another sense. Participants were randomly assigned to a spatial or temporal task that could be performed visually or aurally, which they practiced for five days; before and after training, we measured discrimination thresholds on all four conditions and calculated the extent of transfer between them. Our results show a clear transfer of learning between sensory modalities; however, generalisation was limited to particular conditions. Specifically, learned improvements on the spatial task transferred from the visual domain to the auditory domain, but not vice versa. Conversely, benefits derived from training on the temporal task transferred from the auditory domain to visual domain, but not vice versa. These results suggest a unidirectional transfer of perceptual learning from dominant to non-dominant sensory modalities and place important constraints on models of multisensory processing and plasticity.